Effect Of The Dip And Excavation Orientation On Roof Stability In Moderately Dipping Stone Mine Workings - A. T. Iannacchione (The National Institute for Occupational Safety and Health (NIOSH))
Underground limestone mines typically use the room-and-pillar method of mining in the generally flat-lying limestone formations. In some cases the dip may exceed 5° which can result in unique roof instability problems. Stability may be further exacerbated by the presence of horizontal tectonic stresses. Field studies and numerical model analyses are combined to assess the affect of the dip in various stress conditions. The results showed that where the horizontal tectonic stresses are sufficient to cause intact rock failure, increasing dip results in increased failure potential. The effect of the dip is greater when the maximum horizontal stress is parallel to the dip. Two case studies are presented and evaluated against the findings of stress analysis results. The study showed that the empirical rules of orienting headings parallel to the maximum stress are generally applicable to dipping excavations, except when mining in the up-dip direction. The importance of accurately determining the orientation of the maximum horizontal stress is emphasized because the window of favorable orientations relative to the stress is small.